Trees, seeds and seedlings analyses in the process of obtaining a quality planting material for black locust (Robinia pseudoacacia L.) - Andrea M. ROMAN; Irina M. MORAR; Alina M. TRUTA; Catalina DAN; Adriana F. SESTRAS; Liviu HOLONEC; Florin IORAS; Radu E. SESTRAS (Notulae Scientia Biologicae)
Black locust (Robinia pseudoacacia L.) was among the first North-American tree species imported in Europe. In Romania, black locust has established itself as a forest tree appreciated for multiple uses. The objective of the hereby study was to identify a quality planting material at black locust using seeds from trees with superior traits from five stands geographically close, located in North-western of Romania. An empirical selection was done, thus trees with the most favourable traits were selected as plus trees. Among the averages of the main traits (tree height, diameter at breast height, basal area, self pruning trunk length, crown diameter) of the plus trees from the five stands, there were registered significant differences, and two stands stood out with a high biomass growth. Even if the stands had different ages (between 20-35 year), the age did not influence significantly the growth traits of the trees. The seeds of the plus trees (open-pollinated) from all the stands had large size (mean seed weight of 0.057 g/seed). The seedling emergence rate was high, especially in the solarium condition (between 52.7-73.7% compared with 33.0-41.3% in the field). Coefficient of genetic correlation and heritability calculated for the seedlings belongings to half-sib families highlighted that black locust breeding can be extremely effective by a proper selection.